Investigations on Engineering Properties of Solidified/Stabilized Pb-Contaminated Soil Based on Alkaline Residue. (19th September 2018) - Zha, Fusheng; Pan, Dongdong; Xu, Long; Kang, Bo; Yang, Chengbin; Chu, Chengfu
Abstract : Solidification/stabilization (S/S) has been considered as one of the most effective techniques for remediation of the heavy metal-contaminated sites. Among various binders adopted in S/S, alkaline residue (AR) could be considered as a new binder to treat heavy metal-contaminated soil due to its strong adsorptive capacity for heavy metal ions. So in this paper, the strength, leaching, and microstructure characteristics of the solidified/stabilized Pb-contaminated soil by using alkaline residue are systematically investigated. Test results present that the unconfined compressive strength (UCS) of the treated soil will increase, while the leached Pb 2+ concentration will decrease, with the increase of the alkaline residue content in the specimen. The UCS increases significantly with the curing time increasing during the initial 28 days, after which the UCS of the specimen becomes stable. The leached Pb 2+ concentration decreases significantly at the initial 28 days followed by a stable trend with curing time increasing. The UCS decreases and the leached Pb 2+ concentration increases with the increase of the initial Pb 2+ concentration in the specimen. The microstructural analysis performed by scanning electron microscope (SEM) showed that the increase of the alkaline residue content and curing time will result in more hydration products and densified microstructure, which could effectively improve the engineering properties of the specimen.